Le cluster logistique We4LOG en Occitanie, entre innovation organisationnelle au service de l'intermédiation territoriale et marketing territorial du numérique. - Julien Le Van Suu (Netcom)
Digital innovations like barcodes, RFID chips, GPS tracking, e-commerce and warehouse automation are disrupting the logistics sector and its spatial dimension (Hocquelet, 2021).In Occitania, the logistics professionals needs mismatch institutional discourse (press releases, planning documents, meetings and committees) carried by elected officials and public officers. On the one hand, CEOs and employees put forward the need for "incremental" digital innovations and the need to find other forms of coordination. On the other hand, the institutional discourse highlights the need for disruptive technical innovations such as warehouse automation or motor upgrades (for example with hydrogen). For We4LOG cluster, the topic of digital technology and inclusion of associated actors is not particularly relevant. For now, We4LOG is finding a way across a complex network of actors and building its actions according to the resources available.The analysis is based on an in-depth investigation of the cluster's political backing, the role of local authorities in these initiatives, their objectives and tools. To measure and quantify the gap between the discourse on logistics and practices, the methodology is based on textual statistics of 33 retranscribed semi-directive interviews, press articles and political speeches as well as active observation.